Design of level-basin irrigation systems for robust performance - Reddy, Junna Mohan (American Society of Civil Engineers, 2013)
A well-designed level basin irrigation system is easy to manage and has significant potential for achieving high application efficiency and improved salinity control, particularly when the field is laser-leveled. Over the years, three different criteria have arisen to design level basin irrigation systems. These are the volume-balance design criterion proposed by the Soil Conservation Service of the USDA, the limiting length design criterion, and the completion-of-advance design criterion. For achieving a performance that is close to the design performance, in addition to proper design, a well-defined irrigation schedule must be followed such that the soil moisture deficit at the time of irrigation is close to the design depth. The actual overall performance of a level basin irrigation system will otherwise be lower than the design performance. Using a mathematical simulation model, the performance of a level basin designed using the completion-of-advance design approach was found to be robust relative to one designed using the limiting length approach.